Halmahera and Beyond Social science research in the Moluccas - Visser, Leontine E. (Leiden : Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1994)
LAPIAN (A. B.), Bacan and the Early History of North Maluku
VAN FRAASSEN (Ch. F.), Ternate and its Dependencies
BAKER (J. N.), Ancestral Traditions and State Categories in Tidorese Village Society
GRIMES (B. D.), Buru inside out
PAUWELS (S.), Sibling Relations and (in)Temporality : Towards a definition of the house (Eastern Indonesia)
BARRAUD (C.), Introduction to a Comparative Study of Two Kinship Vocabularies in the Moluccas
MARTODIRDJO (H. S.), Organisasi sosial orang Tugutil di Halmahera
NIJLAND (D. J.), Film en non-verbale cultuuruitingen bij de Tobelo
TELJEUR (D.), Life-Cycle Rituals among the Giman of South Halmahera
VALERI (V.), "Our Ancestors Spoke Little" : Knowledge and social forms in Huaulu
MASINAMBOW (E. K. M.), The Halmahera Research Project and Regional Development
VISSER (L. E.), A Note on Social Science Research Policy
VISSER (L. E.), Bibliography on Moluccan Research since the 1980s
Contient une bibliographie sur la recherche sur les Moluques depuis 1980
bibliogr. dissém.